(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The article analyzes the dynamics of the number of pensioners in the Russian Federation and the average size of the accrued state pension for the period 2015-2019, proposes measures aimed at financial stabilization of the pension system of citizens of the Russian Federation.